Preparation method and application of polyacid salt doped photo-thermal response flexible double-layer hydrogel information compiling robot
The robot material is compiled through photothermal-responsive flexible double-layer hydrogel information incorporated by polyate. Combined with ultraviolet light and temperature response, the shortcomings of the strength and response functions of flexible hydrogel materials in the prior art are solved, and high intensity is achieved , sensitivity and multiple characteristics of information processing.
Patent Information
- Application Number
- CN202410291911.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-03-14
AI Technical Summary
The existing flexible hydrogel robot materials are difficult to take into account high-strength, flexibility, and multiple stimulus response functions, and cannot stably collect, encrypt and output information under complex conditions.
The preparation method of photothermal-responsive flexible double-layer hydrogel information compilation robot is adopted with polyate-incorporated, through raw materials such as N-isopropyl acrylamide, acylation-modified β-cyclodextrin and multi-walled carbon nanotubes. Free radical polymerization and host-guest cross-linking reaction are used to combine ultraviolet light and temperature response to realize information compilation and encryption.
It realizes high mechanical strength, sensitive signal response and reversible information processing of flexible double-layer hydrogel materials, and has excellent flexibility, response anisotropy and information display, transmission and concealment capabilities.
Smart Images

Figure CN119306889A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a double-layer hydrogel with ultraviolet-photothermal response color deformation. Background Art
[0002] Traditional hydrogels are static materials with limited applications due to their single performance and insensitivity to environmental changes. Therefore, stimulus-responsive hydrogels have emerged as a "smart" material. At present, the research on the multi-stimulus response characteristics of hydrogels is becoming more and more complete, and smart response hydrogel sensors have been used in mechanical sensing, speech recognition, health diagnosis, energy collection and signal monitoring. Compared with the pressure-driven and battery-driven traditional robots, hydrogel robots use light and temperature as signal sources, which can realize instantaneous on / off cycle switching of signals, and have the advantages of stable signals, flexible operation, spatial and directional specificity, etc. By micro-loading photothermal active components and covalently binding with the gel network, the reversible reconstruction of the photoresponsive gel network is realized, and the photothermal active components are macroscopically controlled to arrange regularly in the gel network to construct a gradient, and the anisotropic response behavior can be expressed by local light irradiation, which injects new momentum into the innovative research and development of compiler materials. The flexible hydrogel robot materials currently developed and prepared cannot take into account high strength, excellent flexibility, and multiple stimulus response functions, and it is difficult to achieve stable information collection, loading, encryption and output under complex conditions. Therefore, it is urgent to explore new hydrogel synthesis strategies to prepare new flexible hydrogel compilation robot materials that have the special functions of high mechanical strength, sensitive signal response, and strong flexibility. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a preparation method and application of a polyacid-doped photothermal responsive flexible double-layer hydrogel information compilation robot.
[0004] The present invention uses N-isopropylacrylamide and acylated modified β-cyclodextrin as raw materials, mixes into ultrasonically treated multi-walled carbon nanotube dispersion, obtains a photothermal responsive hydrogel matrix I through free radical polymerization and host-guest crosslinking reaction, then utilizes the reversible color change property of polyacid salt under ultraviolet light irradiation, dissolves N-isopropylacrylamide, acylated modified β-cyclodextrin and ammonium molybdate tetrahydrate in deionized water to obtain a mixed reaction liquid, casts the reaction liquid on the photothermal responsive hydrogel matrix I, and utilizes free radical polymerization, electrostatic action and host-guest crosslinking to obtain a photothermal responsive flexible double-layer hydrogel information compiling robot doped with polyacid salt.
[0005] A method for preparing a polyacid-doped photothermal responsive flexible double-layer hydrogel information encoding robot is specifically completed in the following steps:
[0006] 1. Preparation of acylated modified β-cyclodextrin:
[0007] ①, add β-cyclodextrin and potassium hydroxide into deionized water, stir magnetically for a period of time in a water bath at 0℃~4℃ to obtain mixed solution Ⅰ;
[0008] ②, add acryloyl chloride dropwise to the mixed solution I, maintaining magnetic stirring during the addition process, to obtain a mixed solution II;
[0009] ③. Heat the mixed solution II in a water bath and stir it magnetically for a period of time, and then vacuum concentrate it using a rotary evaporator to obtain a concentrated solution;
[0010] ④. The concentrated solution is added dropwise into acetone for precipitation, filtered under reduced pressure, the precipitate is washed with acetone, pre-frozen for a period of time, and then vacuum-freeze-dried for a period of time to obtain acylated modified β-cyclodextrin;
[0011] 2. Preparation of Photothermal Responsive Hydrogel Matrix I:
[0012] ①, weigh multi-walled carbon nanotubes and hexadecyltrimethylammonium bromide, dissolve them in deionized water, and ultrasonicate for a period of time to obtain a multi-walled carbon nanotube dispersion;
[0013] ②, dissolving N-isopropylacrylamide, acylated modified β-cyclodextrin and N',N'-methylenebisacrylamide in deionized water, stirring for a period of time, then adding the multi-walled carbon nanotube dispersion, continuing to stir for a period of time, and then precooling in a -4°C environment to obtain a precooled mixed solution III;
[0014] ③, dissolving potassium persulfate in deionized water to obtain a potassium persulfate aqueous solution; adding the potassium persulfate aqueous solution and N,N,N',N'-tetramethylethylenediamine to the precooled mixed solution III to obtain a precursor solution I;
[0015] ④. Add the precursor liquid I into the silicone mold and place it in a vacuum environment to react for a period of time to obtain a mold containing the photothermal responsive hydrogel matrix I;
[0016] 3. Preparation of a double-layer hydrogel information compilation robot:
[0017] ①, dissolve N-isopropylacrylamide, acylated modified β-cyclodextrin and N',N'-methylenebisacrylamide in deionized water, stir for a while, drop methacryloyloxyethyl trimethylammonium chloride, then add ammonium molybdate tetrahydrate, continue stirring until a uniform and transparent mixed solution is obtained, and precool in a -4°C environment to obtain a precooled mixed solution IV;
[0018] ②, dissolving potassium persulfate in deionized water to obtain a potassium persulfate aqueous solution; adding the potassium persulfate aqueous solution and N,N,N',N'-tetramethylethylenediamine to the precooled mixed solution IV to obtain a precursor solution II;
[0019] ③. Place the precursor liquid II in a mold containing the photothermal responsive hydrogel matrix I, place it in a vacuum environment and let it react for a period of time, demold the hydrogel, and obtain a colloidal mixture;
[0020] ④. Soak and dialyze the colloidal mixture in deionized water to remove unreacted substances, thereby obtaining a polyacid-doped photothermal responsive flexible double-layer hydrogel information compilation robot.
[0021] A photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid is used as a photothermal information acquisition encryptor material with ultraviolet responsive color change and photothermal responsive deformation.
[0022] Principle of the invention:
[0023] The present invention obtains acylated modified β-cyclodextrin through nucleophilic substitution between acryloyl chloride and β-cyclodextrin, uses thermosensitive monomer poly N-isopropylacrylamide and acylated modified β-cyclodextrin as hydrogel skeleton, incorporates photothermal multi-walled carbon nanotubes as photothermal response layer of hydrogel, incorporates ammonium molybdate tetrahydrate as color change layer of hydrogel, and prepares double-layer hydrogel information compiling robot through hydrogen bonding between two layers of hydrogel. Under initial conditions (<20°C and without ultraviolet irradiation), the upper layer of gel loaded with ammonium molybdate tetrahydrate is transparent, while the lower layer is black due to multi-walled carbon nanotubes. At this time, ultraviolet light can be used to irradiate the gel to change the color of the upper layer, but the lower layer is still black, interfering with the color change, and the information content cannot be normally identified. At this time, the gel is heated, and because the upper layer contains hydrophilic monomers, the upper and lower layers of the gel present a dislocated temperature response. At this time, the lower hydrogel undergoes a phase change under heating, and the gel color changes from black to gray, while the upper layer keeps coloring and maintains a certain degree of transparency, and the information can be observed normally. When the temperature rises further and exceeds the phase transition temperature of the upper layer, the transparency of the upper layer gel decreases and cannot be observed normally. The hydrogel robot can display, transmit and hide information.
[0024] Advantages of the present invention:
[0025] 1. The photothermal responsive flexible double-layer hydrogel information compilation robot prepared by the present invention, which is doped with polyacids, adopts the host-guest crosslinking between β-cyclodextrin and poly-N-isopropylacrylamide to form a multi-network interpenetration, and exhibits excellent flexibility;
[0026] Second, the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid prepared by the present invention adds multi-walled carbon nanotubes and N-isopropylacrylamide, showing photothermal responsive deformation characteristics;
[0027] 3. The photothermal responsive flexible double-layer hydrogel information compilation robot prepared by the present invention with the addition of ammonium molybdate tetrahydrate exhibits a reversible ultraviolet responsive color change feature;
[0028] Fourth, the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid prepared by the present invention adopts a double-layer structure of melt casting and exhibits excellent response anisotropy;
[0029] 5. The photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid prepared by the present invention has a high porosity, which is conducive to the movement of free ions and exhibits sensitive signal response characteristics and response stability.
[0030] The invention can obtain a polyacid-doped photothermal response flexible double-layer hydrogel information compiling robot. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a reaction mechanism diagram of step 1 of embodiment 1;
[0032] Figure 2 is a reaction mechanism diagram of step 2 and step 3 of embodiment 1;
[0033] Figure 3 is an infrared spectrum diagram, in which a represents the infrared spectrum curve of β-cyclodextrin, and b represents the infrared spectrum curve of the acylated modified β-cyclodextrin obtained in step 1④ of Example 1;
[0034] Figure 4 is the hydrogen nuclear magnetic resonance spectrum of the acylated modified β-cyclodextrin obtained in step 1④ of Example 1;
[0035] Figure 5 This is a particle size distribution diagram of the multi-walled carbon nanotube dispersion obtained in step ① of Example 1;
[0036] Figure 6 is an infrared spectrum graph, in which a represents the infrared spectrum curve of poly-N-isopropylacrylamide, b represents the infrared spectrum curve of the photothermal responsive hydrogel matrix I obtained in step 2 ④ of Example 1, and c represents the infrared spectrum curve of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with a polyacid obtained in step 3 ④ of Example 1;
[0037] Figure 7 is an X-ray diffraction spectrum, in which a represents the X-ray diffraction curve of the photothermal responsive hydrogel matrix I obtained in step 2 ④ of Example 1, and b represents the red X-ray diffraction spectrum of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3 ④ of Example 1;
[0038] Figure 8 This is a differential scanning calorimetry spectrum of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3④ of Example 1;
[0039] Fig. 9This is a thermogravimetric analysis diagram of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3④ of Example 1;
[0040] Fig.10 This is a scanning electron microscope image of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3④ of Example 1;
[0041] Fig.11 This is a rheological property test diagram of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3④ of Example 1, wherein █ in the figure represents the storage modulus of the hydrogel, and ● in the figure represents the loss modulus of the hydrogel;
[0042] Fig.12 This is a graph showing the tensile stress-strain test results of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3④ of Example 1;
[0043] Fig.13 This is a graph showing the weight variation over time in the degradation test of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3④ of Example 1;
[0044] Fig.14 is a UV-visible spectrum analysis diagram of the hydrogel matrix II prepared in the control example, wherein a is the spectrum line of the hydrogel matrix II prepared in the control example after UV irradiation, and b is the spectrum line of the hydrogel matrix II prepared in the control example without UV irradiation;
[0045] Fig.15 This is the actual effect diagram of the color development / fading process of the hydrogel matrix II prepared in the control example as the concentration of molybdenum ions and the duration of ultraviolet light irradiation change;
[0046] Fig.16 This is a graph showing the absorbance changes with molybdenum ion concentration and ultraviolet irradiation time during the color development of the hydrogel matrix II prepared in the control example, wherein █ in the figure indicates that the molybdenum ion concentration is 1.00 mol / L, ● in the figure indicates that the molybdenum ion concentration is 0.75 mol / L, ▲ in the figure indicates that the molybdenum ion concentration is 0.50 mol / L, ▼ in the figure indicates that the molybdenum ion concentration is 0.25 mol / L, and ◆ indicates that the molybdenum ion concentration is 0 mol / L;
[0047] Fig.17 This is a graph showing the absorbance variation with molybdenum ion concentration and ultraviolet irradiation time of the hydrogel matrix II prepared in the control example after ultraviolet irradiation for 60 seconds and then stopping the irradiation, wherein █ in the figure indicates that the molybdenum ion concentration is 1.00 mol / L, ● in the figure indicates that the molybdenum ion concentration is 0.75 mol / L, ▲ in the figure indicates that the molybdenum ion concentration is 0.50 mol / L, ▼ in the figure indicates that the molybdenum ion concentration is 0.25 mol / L, and ◆ indicates that the molybdenum ion concentration is 0 mol / L;
[0048] Fig.18 : is a graph showing the change in transparency of the hydrogel matrix II prepared in the control example with temperature and time, wherein █ in the graph indicates a temperature of 20°C, ● in the graph indicates a temperature of 40°C, and ▲ in the graph indicates a temperature of 60°C;
[0049] Fig.19 This is a graph showing the change of gel temperature with infrared irradiation time in the infrared response test of the information compiling robot of the photothermal response flexible double-layer hydrogel doped with the polyacid obtained in step 3④ of Example 1;
[0050] Fig. 20 This is a schematic diagram of information load and encryption control of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step three (4) of embodiment one. DETAILED DESCRIPTION
[0051] Specific implementation method 1: In this implementation method, a method for preparing a photothermal responsive flexible double-layer hydrogel information encoding robot doped with polyacid salts is specifically completed according to the following steps:
[0052] 1. Preparation of acylated modified β-cyclodextrin:
[0053] ①, add β-cyclodextrin and potassium hydroxide into deionized water, stir magnetically for a period of time in a water bath at 0℃~4℃ to obtain mixed solution Ⅰ;
[0054] ②, add acryloyl chloride dropwise to the mixed solution I, maintaining magnetic stirring during the addition process, to obtain a mixed solution II;
[0055] ③. Heat the mixed solution II in a water bath and stir it magnetically for a period of time, and then vacuum concentrate it using a rotary evaporator to obtain a concentrated solution;
[0056] ④. The concentrated solution is added dropwise into acetone for precipitation, filtered under reduced pressure, the precipitate is washed with acetone, pre-frozen for a period of time, and then vacuum-freeze-dried for a period of time to obtain acylated modified β-cyclodextrin;
[0057] 2. Preparation of Photothermal Responsive Hydrogel Matrix I:
[0058] ①, weigh multi-walled carbon nanotubes and hexadecyltrimethylammonium bromide, dissolve them in deionized water, and ultrasonicate for a period of time to obtain a multi-walled carbon nanotube dispersion;
[0059] ②, dissolving N-isopropylacrylamide, acylated modified β-cyclodextrin and N',N'-methylenebisacrylamide in deionized water, stirring for a period of time, then adding the multi-walled carbon nanotube dispersion, continuing to stir for a period of time, and then precooling in a -4°C environment to obtain a precooled mixed solution III;
[0060] ③, dissolving potassium persulfate in deionized water to obtain a potassium persulfate aqueous solution; adding the potassium persulfate aqueous solution and N,N,N',N'-tetramethylethylenediamine to the precooled mixed solution III to obtain a precursor solution I;
[0061] ④. Add the precursor liquid I into the silicone mold and place it in a vacuum environment to react for a period of time to obtain a mold containing the photothermal responsive hydrogel matrix I;
[0062] 3. Preparation of a double-layer hydrogel information compilation robot:
[0063] ①, dissolve N-isopropylacrylamide, acylated modified β-cyclodextrin and N',N'-methylenebisacrylamide in deionized water, stir for a while, drop methacryloyloxyethyl trimethylammonium chloride, then add ammonium molybdate tetrahydrate, continue stirring until a uniform and transparent mixed solution is obtained, and precool in a -4°C environment to obtain a precooled mixed solution IV;
[0064] ②, dissolving potassium persulfate in deionized water to obtain a potassium persulfate aqueous solution; adding the potassium persulfate aqueous solution and N,N,N',N'-tetramethylethylenediamine to the precooled mixed solution IV to obtain a precursor solution II;
[0065] ③. Place the precursor liquid II in a mold containing the photothermal responsive hydrogel matrix I, place it in a vacuum environment and let it react for a period of time, demold the hydrogel, and obtain a colloidal mixture;
[0066] ④. Soak and dialyze the colloidal mixture in deionized water to remove unreacted substances, thereby obtaining a polyacid-doped photothermal responsive flexible double-layer hydrogel information compilation robot.
[0067] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that: the mass ratio of β-cyclodextrin and potassium hydroxide in the mixed solution I described in step 1① is 1:(0.2-0.5); the mass fraction of potassium hydroxide in the mixed solution I described in step 1① is 2wt%-4wt%; the speed of magnetic stirring described in step 1① is 600r / min-1200r / min, and the time of magnetic stirring is 5min-15min. The other steps are the same as those in specific implementation method 1.
[0068] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the volume ratio of acryloyl chloride and mixed solution I described in step one ② is (5mL~10mL): (120mL~130mL); the drop rate described in step one ② is 0.3mL / min~1.0mL / min; the speed of magnetic stirring described in step one ② is 600r / min~1200r / min; the temperature of heating and magnetic stirring described in step one ③ is 25℃~55℃, the speed of stirring is 600r / min~1200r / min, and the stirring time is 4h~9h; the temperature of vacuum concentration described in step one ③ is 40℃~70℃, and the concentration is concentrated to 1 / 8~1 / 4 of the original volume. The other steps are the same as specific implementation method one or two.
[0069] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the pre-freezing temperature described in step 1 ④ is -20°C, and the pre-freezing time is 8h to 12h; the vacuum freeze drying temperature described in step 1 ④ is -40°C to -80°C, and the vacuum freeze drying time is 24h to 48h; the mass ratio of the multi-walled carbon nanotubes described in step 2 ① to hexadecyltrimethylammonium bromide is 1:(1 to 3); the mass ratio of the multi-walled carbon nanotubes described in step 2 ① to the volume ratio of deionized water is (20mg to 40mg):10mL; the ultrasonic power described in step 2 ① is 300W to 500W, and the ultrasonic time is 30min to 60min. The other steps are the same as specific embodiments 1 to 3.
[0070] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the mass ratio of N-isopropylacrylamide, N',N'-methylenebisacrylamide and acylated modified β-cyclodextrin described in step 2 ② is (32.5-65):2:1; the stirring time described in step 2 ② is 5min-15min, and the stirring speed is 1000r / min; the mass volume ratio of N-isopropylacrylamide, deionized water and multi-walled carbon nanotube dispersion described in step 2 ② is (0.5g-0.7g):(5mL-10mL):(5mL-15mL); the precooling time described in step 2 ② is 40min-60min. The other steps are the same as those of specific embodiments 1 to 4.
[0071] Specific embodiment six: The difference between this embodiment and specific embodiments one to five is that: the concentration of the potassium persulfate aqueous solution described in step 2③ is 10mg / mL~30mg / mL; the volume ratio of the potassium persulfate aqueous solution, N,N,N',N'-tetramethylethylenediamine and the pre-cooled mixed solution III described in step 2③ is 1mL:(20μL~40μL):(5mL~15mL); the static reaction time described in step 2④ is 24h~48h.
[0072] The other steps are the same as those in Specific Embodiments 1 to 5.
[0073] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the mass ratio of N-isopropylacrylamide, N',N'-methylenebisacrylamide and acylated modified β-cyclodextrin described in step 3① is (32.5-65):2:1; the mass volume ratio of N-isopropylacrylamide, deionized water and methacryloyloxyethyltrimethylammonium chloride described in step 3① is (0.5g-0.8g):(5mL-15mL):(0.1mL-0.5mL); the concentration of ammonium molybdate tetrahydrate in the precooled mixed solution IV described in step 3① is 0.25mol / L-1.00mol / L; the stirring speed described in step 3① is 1000r / min, and the stirring time is 5min-15min; the precooling time described in step 3① is 40min-60min. The other steps are the same as specific embodiments 1 to 6.
[0074] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the concentration of the potassium persulfate aqueous solution described in step three ② is 10 mg / mL to 30 mg / mL; the volume ratio of the potassium persulfate aqueous solution, N,N,N',N'-tetramethylethylenediamine and the precooled mixed solution IV described in step three ② is 1 mL: (20 μL to 40 μL): (10 mL to 25 mL). The other steps are the same as those of specific embodiments one to seven.
[0075] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the volume ratio of the precursor liquid II to the precursor liquid I described in step 3 ③ is (2mL to 5mL): (2mL to 5mL); the time of the static reaction described in step 3 ③ is 24h to 48h; the time of the soaking dialysis described in step 3 ④ is 48h to 96h, the water is changed every 12h, and the molecular weight cut-off of the dialysis bag is 3500 to 5000. The other steps are the same as those of specific embodiments 1 to 8.
[0076] Specific embodiment ten: This embodiment is a photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid salts used as a photothermal information collection and encryption device material with ultraviolet responsive color change and photothermal responsive deformation.
[0077] The following examples are used to verify the beneficial effects of the present invention:
[0078] Embodiment 1: A method for preparing a photothermal responsive flexible double-layer hydrogel information encoding robot doped with polyacid salts is specifically completed by the following steps:
[0079] 1. Preparation of acylated modified β-cyclodextrin:
[0080] ①, add 10.0g of β-cyclodextrin and 3.0g of potassium hydroxide into 125mL of deionized water, stir magnetically for 10min in a water bath at 0℃~4℃, and the speed of magnetic stirring is 1000r / min, to obtain mixed solution I;
[0081] ②, add 7.2 mL of acryloyl chloride dropwise to the mixed solution I at a dropping speed of 0.5 mL / min, and maintain magnetic stirring during the dropping process at a speed of 1000 r / min to obtain a mixed solution II;
[0082] ③. Transfer the mixed solution II to a 40°C water bath, heat it and stir it magnetically for 8 hours at a speed of 1000 r / min, and then evaporate it in a vacuum on a rotary evaporator at 45°C to 1 / 5 of its original volume to obtain a concentrated solution;
[0083] ④. The concentrated solution was added dropwise into acetone for precipitation, filtered under reduced pressure, and the precipitate was washed with acetone for 3 times, pre-frozen for a period of time, and then vacuum-freeze-dried for a period of time to obtain acylated modified β-cyclodextrin;
[0084] The pre-freezing temperature in step 1④ is -20°C and the pre-freezing time is 12h;
[0085] The vacuum freeze drying temperature in step 1④ is -80°C, and the vacuum freeze drying is 48h;
[0086] 2. Preparation of Photothermal Responsive Hydrogel Matrix I:
[0087] ①, weigh 30 mg of multi-walled carbon nanotubes and 30 mg of hexadecyltrimethylammonium bromide and dissolve them in 10 mL of deionized water, and ultrasonicate them at an ultrasonic power of 400 W for 60 min to obtain a multi-walled carbon nanotube dispersion;
[0088] ②, 0.65g N-isopropylacrylamide, 0.01g acylated modified β-cyclodextrin and 20mg N',N'-methylenebisacrylamide were dissolved in 7mL deionized water, stirred at a stirring speed of 1000r / min for 15min, and then the multi-walled carbon nanotube dispersion was added, and the stirring was continued at a stirring speed of 1000r / min for 10min, and then placed in a -4℃ environment for precooling for 60min to obtain a precooled mixed solution III;
[0089] ③. Dissolve 200 mg of potassium persulfate in 10 mL of deionized water to obtain a potassium persulfate aqueous solution with a concentration of 20 mg / mL; add 1 mL of a potassium persulfate aqueous solution with a concentration of 20 mg / mL and 30 μL of N,N,N',N'-tetramethylethylenediamine to the precooled mixed solution III to obtain a precursor solution I;
[0090] ④. Add 5 mL of precursor liquid I into a silicone mold with a size of 5 cm×2 cm×2 cm and place it in a vacuum environment for 24 hours to react, thereby obtaining a mold containing a photothermal responsive hydrogel matrix I;
[0091] 3. Preparation of a double-layer hydrogel information compilation robot:
[0092] ①, 0.65g N-isopropylacrylamide, 0.01g acylated modified β-cyclodextrin and 20mg N',N'-methylenebisacrylamide were dissolved in 10mL deionized water, stirred at a stirring speed of 1000r / min for 15min, 0.2mL methacryloyloxyethyl trimethylammonium chloride was dropped, and then 0.01mol ammonium molybdate tetrahydrate was added, and stirring was continued until a uniform and transparent mixed solution was obtained, and precooled in an environment of -4℃ for 60min to obtain a precooled mixed solution IV;
[0093] ②, dissolve 200 mg of potassium persulfate in 10 mL of deionized water to obtain a potassium persulfate aqueous solution with a concentration of 20 mg / mL; add 1 mL of a potassium persulfate aqueous solution with a concentration of 20 mg / mL and 30 μL of N,N,N',N'-tetramethylethylenediamine to the precooled mixed solution IV to obtain a precursor solution II;
[0094] ③. Place 5 mL of precursor liquid II in a mold containing photothermal responsive hydrogel matrix I, and then place it in a vacuum environment to react for 48 hours, demold the hydrogel to obtain a colloidal mixture;
[0095] ④. Soak the colloidal mixture in 200 mL of deionized water for dialysis, change the water every 12 hours, and repeat the water change 6 times to remove the unreacted substances, and obtain a photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid salts;
[0096] The molecular weight cut-off of the dialysis bag described in step 3④ is 5000.
[0097] Figure 1 is a reaction mechanism diagram of step 1 of embodiment 1;
[0098] pass Figure 1 It can be seen that: in the presence of potassium hydroxide alkaline solution, β-cyclodextrin and acryloyl chloride undergo acylation through a substitution reaction to obtain acylated β-cyclodextrin.
[0099] Figure 2 is a reaction mechanism diagram of step 2 and step 3 of embodiment 1;
[0100] from Figure 2 It can be seen that the acylated β-cyclodextrin and N-isopropylacrylamide form the gel main network skeleton through free radical polymerization and host-guest crosslinking. Hydrogel matrix I and hydrogel matrix II are prepared by respectively incorporating multi-walled carbon nanotubes or ammonium molybdate tetrahydrate into the gel skeleton. The flexible double-layer hydrogel information compilation robot material is obtained by casting the reaction solution and hydrogen bonding.
[0101] Figure 3 is an infrared spectrum diagram, in which a represents the infrared spectrum curve of β-cyclodextrin, and b represents the infrared spectrum curve of the acylated modified β-cyclodextrin obtained in step 1④ of Example 1;
[0102] Depend on Figure 3 It can be seen that at 3400cm -1 The vibration absorption peak of -OH appears at 2920cm -1 The stretching vibration absorption peak of -CH appears at 1150cm -1 and 1180cm -1 The β-CD inner cavity CO and COC stretching vibration absorption peaks are shown in the figure. Comparing the β-CD spectrum with the ACD spectrum ( Figure 3 Spectrum line b) shows that ACD still retains the original cavity structure of β-CD and has a peak at 1720 cm -1 、1210cm -1 、808cm -1 The newly added C=O, CO, and C=C absorption vibration peaks at the wavenumbers indicate that the carbon-carbon double bond was successfully introduced into β-CD with the help of the acetylation reaction.
[0103] Figure 4 is the hydrogen nuclear magnetic resonance spectrum of the acylated modified β-cyclodextrin obtained in step 1④ of Example 1;
[0104] Depend on Figure 4 It can be seen that acryloyl chloride preferentially binds to the primary hydroxyl group ( Figure 4In addition, the peak area integration results showed that about one C=C structure was grafted per unit cyclodextrin, that is, an ACD gel precursor containing one carbon-carbon double bond was obtained, indicating that acetyl-modified β-cyclodextrin was successfully prepared.
[0105] Figure 5 This is a particle size distribution diagram of the multi-walled carbon nanotube dispersion obtained in step ① of Example 1;
[0106] Depend on Figure 5 It can be seen that the particle size distribution range of multi-walled carbon nanotubes is 14 nm to 5.55 μm, the average particle size is 934.867±93.613 nm, and the PDI value is 0.690±0.00495, indicating that the sample is well dispersed.
[0107] Figure 6 is an infrared spectrum graph, in which a represents the infrared spectrum curve of poly-N-isopropylacrylamide, b represents the infrared spectrum curve of the photothermal responsive hydrogel matrix I obtained in step 2 ④ of Example 1, and c represents the infrared spectrum curve of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with a polyacid obtained in step 3 ④ of Example 1;
[0108] Depend on Figure 6 It can be seen that: 3290cm in spectral line a -1 The peak at 2980cm is the stretching vibration peak of the NH bond in the free amino group. -1 and 2930cm -1 Represent the CH stretching vibration peaks of the methyl and methylene groups on PNIPAM, 1640 cm -1 and 1450cm -1 The amide bond C=O vibration peak is represented at 1080 cm-1. Comparing the spectrum line b and the spectrum line c, the main characteristic peaks of poly N-isopropyl acrylamide appear in both spectrum line b and spectrum line c, indicating that the hydrogel matrix I obtained in step 2 ④ of Example 1 and the flexible double-layer hydrogel information compilation robot material obtained in step 3 ④ of Example 1 have similar infrared spectrum characteristics of characteristic functional groups as poly N-isopropyl acrylamide, and both retain the poly N-isopropyl acrylamide skeleton. In addition, spectrum line b and spectrum line c have similar infrared spectrum characteristics at 1080 cm-1. -1 The antisymmetric stretching vibration peak of the oxygen bridge in β-cyclodextrin appears at , which is consistent with the literature, indicating that a flexible double-layer hydrogel compilation robot has been successfully prepared.
[0109] Figure 7 is an X-ray diffraction spectrum, in which a represents the X-ray diffraction curve of the photothermal responsive hydrogel matrix I obtained in step 2 ④ of Example 1, and b represents the red X-ray diffraction spectrum of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3 ④ of Example 1;
[0110] Depend on Figure 7 It can be seen that the two broad diffraction peaks at 8° and 19° in the hydrogel matrix I are characteristic peaks of the amorphous structure of poly-N-isopropylacrylamide, and the broad diffraction peak at 2θ=12° is speculated to be caused by β-cyclodextrin. The diffraction peaks at 2θ=8°, 2θ=12° and 2θ=19° in the spectrum b disappear, and two weak broad diffraction peaks appear at 2θ=10° and 2θ=27°. The X-ray diffraction spectra of the measured materials show broad diffuse scattering peaks, indicating that they have an amorphous structure.
[0111] Figure 8 This is a differential scanning calorimetry spectrum of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3④ of Example 1;
[0112] Depend on Figure 8 It can be seen that due to the volatilization of bound water, the gel robot material experiences the first mass loss at 25°C to about 125°C, with a loss of about 3%; when the temperature continues to rise to 245°C, a significant second mass loss begins to occur, which ends at 400°C. During this process, the interaction between the cyclodextrin host inside the gel and the methyl guest in poly (N-isopropylacrylamide) is overcome, and the carbon-carbon single bonds formed by free radical polymerization cross-linking are cleaved, causing the gel network structure to degrade.
[0113] Fig. 9 This is a thermogravimetric analysis diagram of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3④ of Example 1;
[0114] As can be seen from the figure: the flexible double-layer hydrogel robot material shows two obvious endothermic peaks at 265℃ and 396℃. The endothermic peak at 265℃ is speculated to be the endothermic peak caused by overcoming the host-guest effect, while the endothermic peak at 396℃ is caused by the endothermic peak of the CC bond breaking of the gel skeleton.
[0115] Fig.10 This is a scanning electron microscope image of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3④ of Example 1;
[0116] Depend on Fig.10 It can be seen that: after comparing and analyzing the microscopic morphology of the double-layer hydrogel robot material after magnification of 30 times, 100 times, and 500 times, it can be seen that both types of hydrogels are multi-level aperture three-dimensional network structures with closely connected holes, indicating that the target hydrogel was successfully prepared. The double-layer hydrogel has obvious stratification boundaries and a denser three-dimensional network structure. The incorporation of multi-walled carbon nanotubes and the electrostatic interaction between molybdate ions and methacryloyloxyethyl trimethylammonium chloride increase the cross-linking sites of the gel chain, which increases the cross-linking degree of the hydrogel and makes the network structure tighter.
[0117] Fig.11This is a rheological property test diagram of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3④ of Example 1, wherein █ in the figure represents the storage modulus of the hydrogel, and ● in the figure represents the loss modulus of the hydrogel;
[0118] Depend on Fig.11 It can be seen that the flexible double-layer hydrogel compiled robot material shows the characteristics of elastic behavior being greater than viscous behavior, indicating that the target hydrogel is successfully prepared. In addition, the physical cross-linking strategy of host-guest interaction makes the double-layer hydrogel robot material show a significant upward trend in chain aggregation, storage modulus and loss modulus as the angular frequency increases.
[0119] Fig.12 This is a graph showing the tensile stress-strain test results of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3④ of Example 1;
[0120] like Fig.12 As shown: the maximum stress and maximum tensile strain of the flexible double-layer hydrogel compilation robot material are increased to 42KPa and 1300% respectively, and the toughness value is significantly increased to 26.15MPa, proving that the host-guest interaction between acylated-modified β-cyclodextrin and N-isopropylacrylamide gives the hydrogel good tensile properties.
[0121] Fig.13 This is a graph showing the weight variation over time in the degradation test of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step 3④ of Example 1;
[0122] Depend on Fig.13 It can be seen that after the double-layer hydrogel material of the present invention is immersed in 10mL of 0.01M PBS solution for 30 days, its quality maintenance rate is still higher than 95%, indicating that the target flexible double-layer hydrogel compilation robot does not undergo significant degradation in the external environment, has good stability, and can be used as an in vitro intelligent robot for a long time.
[0123] Comparative Example: Hydrogel Matrix II was prepared according to the following steps:
[0124] 1. Preparation of a double-layer hydrogel information compilation robot:
[0125] ①, 0.65g N-isopropylacrylamide, 0.01g acylated modified β-cyclodextrin and 20mg N',N'-methylenebisacrylamide were dissolved in 10mL deionized water, stirred at a stirring speed of 1000r / min for 15min, 0.2mL methacryloyloxyethyl trimethylammonium chloride was dropped, and then 0.01mol ammonium molybdate tetrahydrate was added, and stirring was continued until a uniform and transparent mixed solution was obtained, and precooled in a -4℃ environment for 60min to obtain a precooled mixed solution Ⅰ;
[0126] ②, dissolve 200 mg of potassium persulfate in 10 mL of deionized water to obtain a potassium persulfate aqueous solution with a concentration of 20 mg / mL; add 1 mL of a potassium persulfate aqueous solution with a concentration of 20 mg / mL and 30 μL of N,N,N',N'-tetramethylethylenediamine to the pre-cooled mixed solution I to obtain a precursor solution II;
[0127] ③. Place 5 mL of precursor liquid II in the mold, and then place it in a vacuum environment to react for 48 hours. De-mold the hydrogel to obtain hydrogel matrix II.
[0128] Fig.14 is a UV-visible spectrum analysis diagram of the hydrogel matrix II prepared in the control example, wherein a is the spectrum line of the hydrogel matrix II prepared in the control example after UV irradiation, and b is the spectrum line of the hydrogel matrix II prepared in the control example without UV irradiation;
[0129] It can be seen from spectrum lines a and b that: the unirradiated hydrogel matrix II spectrum has no obvious absorption peak, while after ultraviolet irradiation, an obvious absorption peak appears in the spectrum with the maximum absorption peak at 730nm, and the gel turns blue, indicating that the hydrogel matrix II is successfully prepared.
[0130] Fig.15 This is the actual effect diagram of the color development / fading process of the hydrogel matrix II prepared in the control example as the concentration of molybdenum ions and the duration of ultraviolet light irradiation change;
[0131] Depend on Fig.15 It can be seen that as the concentration of molybdenum ions increases, the gel coloring becomes faster after ultraviolet irradiation, and the coloring is more stable and the fading time is slower after dark treatment.
[0132] Fig.16 This is a graph showing the absorbance changes with molybdenum ion concentration and ultraviolet irradiation time during the color development of the hydrogel matrix II prepared in the control example, wherein █ in the figure indicates that the molybdenum ion concentration is 1.00 mol / L, ● in the figure indicates that the molybdenum ion concentration is 0.75 mol / L, ▲ in the figure indicates that the molybdenum ion concentration is 0.50 mol / L, ▼ in the figure indicates that the molybdenum ion concentration is 0.25 mol / L, and ◆ indicates that the molybdenum ion concentration is 0 mol / L;
[0133] Fig.17 This is a graph showing the absorbance variation with molybdenum ion concentration and ultraviolet irradiation time of the hydrogel matrix II prepared in the control example after ultraviolet irradiation for 60 seconds and then stopping the irradiation, wherein █ in the figure indicates that the molybdenum ion concentration is 1.00 mol / L, ● in the figure indicates that the molybdenum ion concentration is 0.75 mol / L, ▲ in the figure indicates that the molybdenum ion concentration is 0.50 mol / L, ▼ in the figure indicates that the molybdenum ion concentration is 0.25 mol / L, and ◆ indicates that the molybdenum ion concentration is 0 mol / L;
[0134] Fig.16 and Fig.17 It can be seen from the graph of the absorbance variation with molybdenum ion concentration and ultraviolet irradiation (darkness) treatment time during the color development (fading) process of the hydrogel matrix II prepared in the control example that the absorbance of the gel increases with the increase of molybdenum ion concentration in the first 30 seconds of irradiation. When the irradiation continues, the gel sample with a molybdenum ion concentration of 1.00 mol / L has the highest absorbance, and the detection accuracy of the microplate reader decreases. At this time, the irradiation is stopped and the sample is placed under ambient conditions to observe and detect the fading of the gel. When the molybdenum ion concentration is lower than 0.50 mol / L, although the gel shows good color development behavior, the coloring is unstable, and the gel fades significantly after about 30 minutes of dark box treatment; when the molybdenum ion concentration is 0.75 mol / L and 1.00 mol / L, the gel can be maintained for more than 3 hours after coloring, indicating that an appropriate increase in molybdenum ion concentration can enhance the color stability of the gel.
[0135] Fig.18 : is a graph showing the change in transparency of the hydrogel matrix II prepared in the control example with temperature and time, wherein █ in the graph indicates a temperature of 20°C, ● in the graph indicates a temperature of 40°C, and ▲ in the graph indicates a temperature of 60°C;
[0136] When the water bath temperature is between 20℃ and 40℃, ultraviolet light irradiation induces the reduction and coloration of molybdenum ions inside the gel matrix II, and the gel transmittance decreases significantly by about 15%. When the light is removed, the gel fades and the transparency is about 90%. In addition, during 10 cycles of irradiation, the transparency error is maintained within 3%, indicating that the light response color development has good stability. However, when the gel temperature reaches 60℃, the temperature exceeds the phase transition temperature, and the gel network changes to a hydrophobic state, which can reduce the overall transmittance of the gel. Therefore, during the cyclic irradiation process, its transmittance does not change significantly. The above conclusions provide a basis for asynchronous temperature response for the subsequent information encryption of flexible double-layer robots.
[0137] Fig.19 This is a graph showing the change of gel temperature with infrared irradiation time in the infrared response test of the information compiling robot of the photothermal response flexible double-layer hydrogel doped with the polyacid obtained in step 3④ of Example 1;
[0138] Depend on Fig.19 It can be seen that the hydrogel material of the present invention has a significant temperature change after infrared light irradiation. The temperature increases by 8.29°C in the first 300s, and the heating rate is relatively fast. The heating rate of the gel slows down from 300s to 600s. After the irradiation time continues to 600s, the gel temperature does not show a significant change, which has good photothermal performance.
[0139] Fig. 20 This is a schematic diagram of information load and encryption control of the photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid obtained in step three (4) of embodiment one.
[0140] As shown in the figure, under the initial state (temperature < 20°C and no UV irradiation), the upper layer of the gel is transparent, while the lower layer is black due to the multi-walled carbon nanotubes. At this time, the gel can be irradiated with UV light to change the color of the hydrogel matrix II layer, but the lower layer of the hydrogel matrix I interferes with the color change and the information content cannot be normally identified. At this time, the gel is heated. Since the hydrogel matrix II contains the hydrophilic monomer methacryloyloxyethyl trimethyl ammonium chloride, the upper and lower layers of the gel show a staggered temperature response. At this time, the lower layer of the hydrogel matrix I undergoes a phase change due to heat, and the gel color changes from black to gray, while the upper layer remains colored and maintains a certain degree of transparency. At this time, the information can be observed normally. Further heating exceeds the phase transition temperature of the hydrogel matrix I, and the transparency of the upper layer of the gel decreases, and it cannot be observed normally. However, by controlling the temperature to restore the gel to the initial state, the information compilation can be reversible at this time, and participate in a new round of information compilation, so as to form graphic images and text on the surface of the hydrogel, and use the photothermal response characteristics of images or text to realize the information display, transmission and hiding capabilities of the flexible double-layer hydrogel machine compiler.
Claims
1. A method for preparing a photothermal responsive flexible double-layer hydrogel information encoding robot doped with polyacid salts, characterized in that The preparation method is specifically completed according to the following steps:
1. Preparation of acylated modified β-cyclodextrin: ①, add β-cyclodextrin and potassium hydroxide into deionized water, stir magnetically for a period of time in a water bath at 0℃~4℃ to obtain mixed solution Ⅰ; ②, add acryloyl chloride dropwise to the mixed solution I, maintaining magnetic stirring during the addition process, to obtain a mixed solution II; ③. Heat the mixed solution II in a water bath and stir it magnetically for a period of time, and then vacuum concentrate it using a rotary evaporator to obtain a concentrated solution; ④. The concentrated solution is added dropwise into acetone for precipitation, filtered under reduced pressure, the precipitate is washed with acetone, pre-frozen for a period of time, and then vacuum-freeze-dried for a period of time to obtain acylated modified β-cyclodextrin; 2. Preparation of Photothermal Responsive Hydrogel Matrix I: ①, weigh multi-walled carbon nanotubes and hexadecyltrimethylammonium bromide, dissolve them in deionized water, and ultrasonicate for a period of time to obtain a multi-walled carbon nanotube dispersion; ②, dissolving N-isopropylacrylamide, acylated modified β-cyclodextrin and N',N'-methylenebisacrylamide in deionized water, stirring for a period of time, then adding the multi-walled carbon nanotube dispersion, continuing to stir for a period of time, and then precooling in a -4°C environment to obtain a precooled mixed solution III; ③, dissolving potassium persulfate in deionized water to obtain a potassium persulfate aqueous solution; adding the potassium persulfate aqueous solution and N,N,N',N'-tetramethylethylenediamine to the precooled mixed solution III to obtain a precursor solution I; ④. Add the precursor liquid I into the silicone mold and place it in a vacuum environment to react for a period of time to obtain a mold containing the photothermal responsive hydrogel matrix I; 3. Preparation of a double-layer hydrogel information compilation robot: ①, dissolve N-isopropylacrylamide, acylated modified β-cyclodextrin and N',N'-methylenebisacrylamide in deionized water, stir for a while, drop methacryloyloxyethyl trimethylammonium chloride, then add ammonium molybdate tetrahydrate, continue stirring until a uniform and transparent mixed solution is obtained, and precool in a -4°C environment to obtain a precooled mixed solution IV; ②, dissolving potassium persulfate in deionized water to obtain a potassium persulfate aqueous solution; adding the potassium persulfate aqueous solution and N,N,N',N'-tetramethylethylenediamine to the precooled mixed solution IV to obtain a precursor solution II; ③. Place the precursor liquid II in a mold containing the photothermal responsive hydrogel matrix I, place it in a vacuum environment and let it react for a period of time, demold the hydrogel, and obtain a colloidal mixture; ④. Soak and dialyze the colloidal mixture in deionized water to remove unreacted substances, thereby obtaining a polyacid-doped photothermal responsive flexible double-layer hydrogel information compilation robot.
2. The method for preparing a polyacid-doped photothermal responsive flexible double-layer hydrogel information encoding robot according to claim 1, characterized in that The mass ratio of β-cyclodextrin and potassium hydroxide in the mixed solution I described in step 1① is 1:(0.2~0.5); the mass fraction of potassium hydroxide in the mixed solution I described in step 1① is 2wt%~4wt%; the speed of magnetic stirring described in step 1① is 600r / min~1200r / min, and the time of magnetic stirring is 5min~15min.
3. The method for preparing a polyacid-doped photothermal responsive flexible double-layer hydrogel information encoding robot according to claim 1, characterized in that The volume ratio of acryloyl chloride to mixed solution I described in step 1 ② is (5mL~10mL):(120mL~130mL); the dropping speed described in step 1 ② is 0.3mL / min~1.0mL / min; the speed of magnetic stirring described in step 1 ② is 600r / min~1200r / min; the temperature of heating and magnetic stirring described in step 1 ③ is 25℃~55℃, the stirring speed is 600r / min~1200r / min, and the stirring time is 4h~9h; the temperature of vacuum concentration described in step 1 ③ is 40℃~70℃, and the concentration is concentrated to 1 / 8~1 / 4 of the original volume.
4. The method for preparing a polyacid-doped photothermal responsive flexible double-layer hydrogel information encoding robot according to claim 1, characterized in that The pre-freezing temperature described in step 1④ is -20°C, and the pre-freezing time is 8h to 12h; the vacuum freeze-drying temperature described in step 1④ is -40°C to -80°C, and the vacuum freeze-drying time is 24h to 48h; the mass ratio of the multi-walled carbon nanotubes described in step 2① to hexadecyltrimethylammonium bromide is 1:(1~3); the mass ratio of the multi-walled carbon nanotubes described in step 2① to the volume ratio of deionized water is (20mg~40mg):10mL; the ultrasonic power described in step 2① is 300W~500W, and the ultrasonic time is 30min~60min.
5. The method for preparing a polyacid-doped photothermal responsive flexible double-layer hydrogel information encoding robot according to claim 1, characterized in that The mass ratio of N-isopropylacrylamide, N',N'-methylenebisacrylamide and acylated modified β-cyclodextrin described in step 2② is (32.5-65):2:1; the stirring time described in step 2② is 5min-15min, and the stirring speed is 1000r / min; the mass volume ratio of the mass of N-isopropylacrylamide, deionized water and multi-walled carbon nanotube dispersion described in step 2② is (0.5g-0.7g):(5mL-10mL):(5mL-15mL); the precooling time described in step 2② is 40min-60min.
6. The method for preparing a polyacid-doped photothermal responsive flexible double-layer hydrogel information encoding robot according to claim 1, characterized in that The concentration of the potassium persulfate aqueous solution described in step 2③ is 10mg / mL to 30mg / mL; the volume ratio of the potassium persulfate aqueous solution described in step 2③, N,N,N',N'-tetramethylethylenediamine and the pre-cooled mixed solution III is 1mL:(20μL~40μL):(5mL~15mL); the static reaction time described in step 2④ is 24h~48h.
7. The method for preparing a polyacid-doped photothermal responsive flexible double-layer hydrogel information encoding robot according to claim 1, characterized in that The mass ratio of N-isopropylacrylamide, N',N'-methylenebisacrylamide and acylated modified β-cyclodextrin described in step 3① is (32.5-65):2:1; the mass volume ratio of N-isopropylacrylamide, deionized water and methacryloyloxyethyltrimethylammonium chloride described in step 3① is (0.5g-0.8g):(5mL-15mL):(0.1mL-0.5mL); the concentration of ammonium molybdate tetrahydrate in the precooled mixed solution IV described in step 3① is 0.25mol / L-1.00mol / L; the stirring speed described in step 3① is 1000r / min, and the stirring time is 5min-15min; the precooling time described in step 3① is 40min-60min.
8. The method for preparing a polyacid-doped photothermal responsive flexible double-layer hydrogel information encoding robot according to claim 1, characterized in that The concentration of the potassium persulfate aqueous solution described in step 3② is 10 mg / mL to 30 mg / mL; the volume ratio of the potassium persulfate aqueous solution described in step 3②, N,N,N',N'-tetramethylethylenediamine and the pre-cooled mixed solution IV is 1 mL:(20 μL to 40 μL):(10 mL to 25 mL).
9. The method for preparing a polyacid-doped photothermal responsive flexible double-layer hydrogel information encoding robot according to claim 1, characterized in that The volume ratio of precursor liquid II to precursor liquid I described in step 3③ is (2mL~5mL):(2mL~5mL); the static reaction time described in step 3③ is 24h~48h; the immersion dialysis time described in step 3④ is 48h~96h, the water is changed every 12h, and the molecular weight cutoff of the dialysis bag is 3500~5000.
10. Application of the photothermal responsive flexible double-layer hydrogel information encoding robot doped with polyacid prepared by the preparation method of claim 1, characterized in that The photothermal responsive flexible double-layer hydrogel information compilation robot doped with polyacid salts is used as a photothermal information collection and encryption device material with ultraviolet responsive color change and photothermal responsive deformation.
Citation Information
Patent Citations
Method for preparing temperature sensitive hydrogel with supramolecular structure
CN101092471A
Chitosan-based self-repairing hydrogel and preparation method thereof
CN112961375A
Carboxymethyl cellulose / beta-cyclodextrin temperature-sensitive hydrogel with high mechanical strength and high moisture retention as well as preparation method and application of carboxymethyl cellulose / beta-cyclodextrin temperature-sensitive hydrogel
CN115957151A
Preparation method and application of pH and light dual-response beta-cyclodextrin gel
CN117264142A
Temperature-responsive material and composition comprising the same
JP2003252936A